2013
DOI: 10.1149/2.018311jss
|View full text |Cite
|
Sign up to set email alerts
|

Role of Guanidine Carbonate and Crystal Orientation on Chemical Mechanical Polishing of Ruthenium Films

Abstract: Ruthenium (Ru) films deposited on either TiN or TaN/Ta have been proposed as a barrier stack in advanced interconnects. Here, we investigated their polishing behavior using colloidal silica-based slurries containing guanidine carbonate (GC) or hydrogen peroxide (H2O2) or both. Neither GC nor H2O2 alone enhanced the Ru removal rates (RRs) but their combination did, presumably, due to the formation of Ru oxide-guanidinium complexes which can be polished by silica abrasives suggesting that the oxidation of Ru to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 57 publications
3
49
0
Order By: Relevance
“…As mentioned by Amanapu et al, 15 Ru oxides/hydroxides likely form complexes with guanidinium ions in the presence of GC and KMnO 4 at pH 10. These complexes are then polished away by silica abrasives at a down pressure of only 2 psi.…”
Section: 25mentioning
confidence: 70%
“…As mentioned by Amanapu et al, 15 Ru oxides/hydroxides likely form complexes with guanidinium ions in the presence of GC and KMnO 4 at pH 10. These complexes are then polished away by silica abrasives at a down pressure of only 2 psi.…”
Section: 25mentioning
confidence: 70%
“…30 However, Amanapu et al 15 did not investigate the possibility of galvanic corrosion at the Ru/Cu bimetallic interface as well as maintaining an adequate removal rate selectivity of Ru to Cu. In this paper, we describe the results of the studies of the corrosion behaviors of Ru and Cu, using open circuit potential (E OC ) measurements and potentiodynamic polarization experiments, in H 2 O 2 and GC-based solutions at pH 9, a value chosen to avoid the formation of toxic RuO 4.…”
Section: -29mentioning
confidence: 99%
“…13,14 Of these, Ru/TiN structures were chosen for the analysis here since Amanapu et al 15 have shown that these films are polished faster compared to those on TaN. They attributed this to the difference in the crystalline orientation of the Ru films deposited on TiN and TaN layers.…”
mentioning
confidence: 99%
See 2 more Smart Citations